Pemanfaatan Sosial Media Sebagai Sarana Pemasaran di Era Digital Pada Tas Anyaman Di Dukuh Krajan Desa Sukorejo - Ulfa, Adela Ulifatul; Fathoni, Khoirul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
With the rapid progress of the internet, exchanging information has become easier and faster. As a result, people turn to the internet for communication and interaction. Social media, with its various benefits, is becoming a valuable tool for businesses to promote their products and services. This activity aims to understand how to utilize social media as a product promotion channel to reach consumers, identify obstacles in product promotion using social media, and find effective solutions to maximize social media as a promotional medium. This activity used the Asset-based community development (ABCD) method and succeeded in identifying a number of obstacles. This activity also provides practical solutions, such as using social media Facebook, Instagram and WhatsApp as promotional channels for the woven bag business. By using social media in Dukuh Krajan, sales of Mrs. Nikmah's woven bags will increase significantly.